PELAKSANAAN PEMBINAAN AKHLAK DALAM PEMBELAJARAN BAGI SISWA TUNAGRAHITA - Ria Andriani (Universitas Negeri Padang, 2014)
Good morals, attitudes and atigues are sone necessary in our daily lives. This research was based on (our) national effort to create next generations who have those crucial values. Study was conducted in special need education school (SLB) Muhammadiyah Pauh IX Padang. Researcher used descriptive method to describe the facts collected during study date were gathered through observation, interview, documentation (file) study were techer and students in SLB Muhammadiyah Pauh IX Padang. Result showed that moral education had not been maximally executed. Teacher did not teach moral values during teaching learning process. Teacher faced challenges in implementing and keeping the values during instruction. However they had given their to do so. It is suggested that teachers increase their effort so that studens especially special need students perform bettet attitude and moral that are more acceptable in society. Keyword : Intellectual disability , Learning, moral.